A Comparative Study of the Meditation Techniques between Thai and Chinese Buddhist Traditions - Xiaoli, Lei (Journal of International Buddhist Studies, 2016)
This is a comparative study of the meditation techniques between Thai and Chinese Buddhist traditions. On the ground of the knowledge of meditation practices in Pali and Chinese Buddhist canon and meditation techniques prevalent in Thailand and China, this research is to find the similarities and differences between them in way to organize meditation practice, the theoretical basis for meditation techniques, and similar meditation techniques in these two Buddhist traditions. This research finds that both Thai and Chinese meditation masters try to bring meditation into normal people’s daily life, by making meditation centers easily to reach, reducing the importance of studying scriptures, and leading meditators’ being confidence in Nibbana. However, there are also some differences between the meditation techniques in Thai and Chinese Buddhist Traditions. In Thailand, meditation courses are normally organized by meditation centers, while in China, temples are organizing meditation practices. What is more, though there are some similar meditation techniques in these two Buddhist traditions, such as contemplation on breathing, as well as recitation of “Boddho” and Nian-fo, they are from different Buddhist texts and belonging to different meditation subjects.